The Plights of Females in Passion by Alice Munro - Fan, Zixuan (Transactions on Social Science, Education and Humanities Research, 2024)
By the study of a collection of novel runaways, the paper can discover the Alice Munro depicts the growth process where some traditional women never give up seeking for the ideal life style in the patriarchal system. Thus, this thesis aims to discuss women’s growth process in Runaway to explore self-pursuit of women’s ideal life style and self-realization process from the perspective of feminism criticism involving a series of topics, such as voice right, self-consciousness, and gender issues. It not only provides new perspective of the study about Munro’s works, but also it is beneficial for readers to capture the profound connotation and to enjoy the artistic charm.